(untitled) (Cardiovascular Journal, 2017)
Background: Coronary dominance affects on in-hospital outcomes of patients with acute coronary syndrome and also affects the outcome following percutaneous coronary intervention. Left dominant anatomy is believed to be associated with worse prognoses for patients with acute coronary syndrome undergoing percutaneous coronary. This study evaluated the manner in which coronary dominance affects in-hospital adverse outcomes of acute coronary syndrome (ACS) patients who underwent percutaneous coronary intervention (PCI). Methods: Data were analyzed from 149 ACS patients who underwent PCI between November 2014 and October 2015 at National Institute of Cardiovascular Diseases (NICVD), Dhaka. The patients were grouped based on diagnostic coronary angiograms performed prior to PCI; those with right dominant plus co-dominant anatomy (RD+Co group) and those with left dominant anatomy (LD group). Results: Total adverse in-hospital outcome is 8.7% patients. In LD group 23.1% patients were experienced adverse in-hospital outcome, on the contrary 5.7% of the patients with RD+Co group did have such experience. About 2.7% patients developed arrhythmia, 2.7% cardiogenic shock, 2% acute left ventricular failure and 0.7% ischaemic chest pain of the both groups. Among them arrhythmia, acute left ventricular failure and cardiogenic shock were more common in LD group than RD+Co (7.7% vs. 1.6%, 7.7% vs. 0.8% and 7.7% vs. 1.6%) group. Multivariate logistic regression analysis revealed that smoking, diabetes mellitus and left coronary dominance were the independent predictors for developing adverse in-hospital outcome with ORs being 1.317, 1.074 and 6.553 respectively (p <0.05). Conclusion: Patients of left coronary dominant had higher in-hospital adverse outcome compared with patients of right dominant plus co-dominant in a population with acute coronary syndrome who underwent percutaneous coronary intervention and left dominant anatomy was an independent predictor for developing adverse in-hospital outcome. Cardiovasc. j. 2017; 9(2): 129-134